Training schedule and sleep in adolescent swimmers - Gudmundsdottir, S. L. (Pediatric Exercise Science, 2020)
Purpose: Insufficient sleep duration may affect athletic performance and health. Inconsistent sleep pattern also has negative health effects, but studies on athletes` intraindividual sleep variability are scarce. The aim of this research was to compare total sleep time (TST) and variability (TST-variability), wakening after sleep onset, and sleep efficiency, during nights preceding early morning practices with other nights, and to investigate sleep characteristics of nights following a day with early morning only, evening only, or both a morning and an evening session in adolescent swimmers. Methods: Wrist-worn accelerometers were used to measure 1 week of sleep in 108 swimmers (mean age 16.1 [2.6] y) in Iceland. Adjusted regression analyses and linear mixed models were used to explore associations of training schedules with TST, TST-variability, wakening after sleep onset, and sleep efficiency. Results: Mean TST was 6:32 (h:min) (±39 min) and TST-variability was 63 minutes (±25 min). TST decreased and TST-variability increased with more early morning practices. TST preceding early training was 5:36 and 5:06 in <16- and =16-year-olds, respectively, shorter than on nights preceding later or no morning training (P<.001). Conclusion: Swimmers have extremely short TST preceding early morning sessions and increased TST-variability with more early morning sessions.